1998
DOI: 10.1097/00005650-199801000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Case Managed Residential Care for Homeless Addicted Veterans

Abstract: Within groups, significant improvements were observed with time from baseline to all posttests on the four major outcomes. We learned, however, that veterans had access to and used significant amounts of services even without the special case-managed residential care program. This partially may account for improvements in the control group and may have muted the differences between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 9 publications
1
60
0
1
Order By: Relevance
“…Persons with substance abuse problems who were assessed but had not yet attended their first clinical appointment have received services from case managers in centralized intake units (Carr et al, 2008;Scott et al, 2002). In-treatment case management has stressed retention in treatment as well as improvement in substance use, criminal justice involvement, and a variety of other outcomes (Conrad et al, 1998;Cox et al, 1998;Saleh et al, 2003). In order to maintain gains made while in treatment, case management has also received attention as an important part of the aftercare period (Siegal, Li, & Rapp, 2002).…”
Section: Role In the Continuum Of Carementioning
confidence: 99%
“…Persons with substance abuse problems who were assessed but had not yet attended their first clinical appointment have received services from case managers in centralized intake units (Carr et al, 2008;Scott et al, 2002). In-treatment case management has stressed retention in treatment as well as improvement in substance use, criminal justice involvement, and a variety of other outcomes (Conrad et al, 1998;Cox et al, 1998;Saleh et al, 2003). In order to maintain gains made while in treatment, case management has also received attention as an important part of the aftercare period (Siegal, Li, & Rapp, 2002).…”
Section: Role In the Continuum Of Carementioning
confidence: 99%
“…Altogether, 61% of participants whose predominant residential status prior to intake was homeless (literal or marginal) were residentially stable at 36 months. This is particularly notable because prior research suggests that homeless substance abusers that are helped into housing by treatment programs often fail to keep it (Braucht et al, 1995;Burnam et al, 1995;Conrad et al, 1998), in part due to high rates of relapse and its consequences.…”
Section: All Homeless (N = 287)mentioning
confidence: 99%
“…In contrast, a more focused, agency-specific approach, in which pairs of agencies map out specific ways of coordinating their efforts, increased access of homeless veterans to social security benefits 3 and improved their quality of life. 4 Clinical services for this population have included (1) community outreach, 5 (2) case management, [6][7][8] and (3) housing assistance involving either time-limited halfway house treatment 9,10 or longerterm mainstream community housing with support. 11,12 Recently, experimental studies [6][7][8][9][10][11][12][13][14] have demonstrated superior outcomes for diverse interventions, typically described as supported housing programs in which case management and housing resources are combined, with benefits more often demonstrated for housing outcomes than for clinical status.…”
mentioning
confidence: 99%